Perilaku Konsumsi Islami Masyarakat Muslim Surabaya yang Terdampak Pandemi Covid-19 - Maulana, Luqman; Fikriyah, Khusnul (Jurnal Ekonomika dan Bisnis Islam, 2021)
The raise of covid-19 case in East Java have the government to enforce PSBB (Local Lockdown Policy), nevertheless this policy makes peoples spend more money on some particular product. This condition is known as panic buying. In Islam, people are forbidden to have a massive consumption for their own. Its explained in Q.S. Al-Araf (31). To know the consumption behaviour of muslim that having issue on their economy aspect because of covid-19 is the purpose of this study. This is a quantative study with survey method. This study uses validation test, reliability test, and descriptive statistic analysis through tendency variable table. The result of this study explains that the consumption behaviour of muslim in Surabaya that having economic issue because of covid-19 does not contrary to Islamic values.